The effect of compensation on the performance of KFC Pettarani employees - Dahlan, Abd Halim; Ruma, Zainal; Haeruddin, Muhammad Ilham Wardhana; Akbar, Abdi; Natsir, Uhud Darmawan (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
This study aims to determine the effect of compensation on the performance of KFC Pettarani employees either partially or simultaneously. The number of respondents in this study were 44 KFC Pettarani employees. The sampling technique uses saturated sampling technique. The collection of data used is a questionnaire, documentation, and observation. The analytical method in this study used multiple linear regression analysis which previously carried out validity tests, reliability tests, classic assumption tests (normality test, multicollinearity test, heteroscedasticity test), coefficient of determination test, t test, and f test.The results showed that partially financial compensation has a positive and significant effect on employee performance with a sig value of 0.005 (<0.05). While non-financial compensation partially has no positive and significant effect on employee performance with a sig value of 0.295 (> 0.05). As for simultaneously, financial compensation and non-financial compensation have a positive and significant effect on employee performance with a sig value of 0.000.